STRATEGIC BLINDNESS: HOW BANNING TECHNOLOGY WITHOUT ALTERNATIVES INVITES ECONOMIC RECESSION AND SOVEREIGNTY RISKS - Kharal, Shafiq (The journal of contemporary issues in business and government, 2025)
This paper points out the strategic, economic, and sovereignty risks of banning foreign-made technology without an adequate domestic alternative. The thesis, informed by the research of Hassan Rasheed Siddiqui, an authority on aviation law and policy, is that such bans, usually predicated on national security considerations, inevitably result in unintended consequences, presenting them open to economic recession, technological dependence and political coercion. The study cites three key risks associated with banning foreign technologies: price inflation because of monopolistic behavior, supply chain delays based on failing to find domestic masters of the technology previously supplied by foreigners, and system disruption from the failure of locked-in legacy systems that were dependent on the banned technologies. This study underlines the significance of proactive technology transition policies and mechanisms, such as the promotion of domestic innovation, the formulation of legislation-based technology shifting roadmaps, and public and industry education in handling these sorts of transitions. Furthermore, the paper provides specific policy suggestions for how to manage the risks associated with such foreign technology bans. Then it goes on with: “The recommended measures include the development of a neutral, sovereign tech production, the setting up of strategic tech-buffer reserves, the introduction of appropriate regulatory measures and legislative precautions against tech blackmail. Emphasizing long-term resilience, national sovereignty and innovation, the research brings to the fore the need for governments act strategically when planning for technology transitions, so as to avoid the inadvertent creation of points of technological and economic weakness.